Critical Book Review: Maritime Security Complexes Of The Indo-Pacific Region - Pandey, Shivam Kumar (International Journal of Psychosocial Rehabilitation, 2025)
The Book "Maritime Security Complexes of the Indo-Pacific Region" is authored by Dr Vijay Sakhuja, who holds MPhil and PhD degrees from Jawaharlal Nehru University in New Delhi. Dr Sakhuja is a former Director of the National Maritime Foundation in New Delhi and a former officer of the Indian Navy. The co-author, Dr W. Lawrence S. Prabhakar, is a researcher and professor specializing in International Relations and Strategic Studies. He was previously associated with the Department of Political Science at Madras Christian College. The publication emerged towards the conclusion of 2022 and pertained to maritime strategic and national security literature. Its primary focus lies in exploring theoretical perspectives concerning the advancements within the Indo-Pacific maritime security sphere. It assesses regional challenges and opportunities around Indo-Pacific security and is visualized through complex regional security theory lenses. It reveals the highly tense emerging order in the Indo-Pacific maritime zones. The fusion of academic expertise and practical viewpoints will stimulate analytical thought and aid India in formulating, expressing, and constructing maritime doctrines specifically designed to effectively address the current and future dynamics of the Indo-Pacific region. The contemporary issues raised in the book deal with the Indo-pacific challenges and opportunities which come at a time when it is becoming the more contested space both from the economic and strategic point of view. The Book relies on the pretext that the geopolitical framework known as the Indo-Pacific Region has gradually developed over the past decade. In 2007, the former Prime Minister of Japan, Shinzo Abe, highlighted the increasing closeness between Japan (symbolized by the Pacific Ocean) and India (symbolized by the Indian Ocean) during his address to the Indian Parliament. Abe characterized the convergence of these two seas as a vibrant combination of freedom and prosperity, with the Indian and Pacific Oceans forming a cohesive entity with discernible geographic boundaries. While initially discussed within the context of India-Japan relations, the concept of the Indo-Pacific Region has since solidified within the global order.